The Impact of Service Quality, Price, and Brand Image on Consumer Loyalty at Yamaha Motor Workshops in Bekasi - Misbahul Anwar; Muhammad Syarif Hidayatullah Elmas; Andrian (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine whether there is a partial and simultaneous significant effect between service quality, price, and brand image on consumer loyalty at Yamaha Motor Workshops in Bekasi. This research method uses a quantitative descriptive approach, the data collection used in this study are the google form questionnaires that distributed to their consumers, data analysis techniques using classical assumption techniques, multiple linear regression, T-test and F-test to test and prove the hypothesis of this study using the SPSS application, using incidental sampling technique methods with a sample of 150 respondents. This study found that the variables of service quality, price, and brand image together have a significant effect on consumer loyalty.